A Study on the risk-return characteristics and the diversification benefit of the Hedge Fund industry - Bagaria, Neha (2007)
Hedge funds with their dynamic trading strategies have gained great popularity in the past decade and have been found to provide significant diversification benefits to a traditional portfolio of assets. As an investment strategy they assure higher returns at a lower risk. Thus we will investigate its unique characteristics and its relation with the S&P 500 index through various quantitative tools like simple regression analysis, Sharpe ratios and graphical and correlation analysis of the different strategies among themselves and with the market. Further we will highlight the importance of the Fund of Hedge Funds which has been found to be more useful in this alternative investment industry than in the world of traditional funds like mutual funds. Since hedge funds are secretive about their activities and as private partnerships are free from disclosure and reporting requirements the data is not readily available and for our work we will utilize 18 hedge fund indices of the Barclay Database which is known to be reliable and available. The results does show majority of the strategies to posses the unique and dynamic characteristics to be in line with previous research but the biases and other problems discussed make the conclusions less objective. Nevertheless we predict a bright future for this industry.